Learning to save tax-efficiently: Tax misperceptions and the effect of informational tax nudges on retirement savings - Kay Blaufus; Michael Milde (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
Using a series of laboratory experiments, this paper studies the effect of tax misperceptions on retirement savings and examines whether informational tax nudges and changing the form of the tax subsidy promote tax-efficient savings behavior. We find that deferred pension taxation results in after-tax pensions that are approximately 25% lower compared to an economically equivalent immediate pension tax system. This indicates substantial tax misperceptions. For subjects with low tax and financial knowledge, these misperceptions remain stable even if they have gained experience. Only if we provide subjects with recurrent numerical informational nudges on tax refunds, together with numerical informational nudges on future pension taxes, do tax distortions disappear for all subjects. Regarding the form of the tax subsidy, we demonstrate that replacing the tax deductibility of retirement savings with matching contributions increases tax-efficiency without the need to provide informational tax nudges.
Keywords: D91; G4; H20; H30; 330; Pension Taxation; Tax Misperception; Learning Behavior; Informational Tax Nudges; Matching Contribution